Normalizing images in various weather and lighting conditions using Pix2Pix GAN - Tasnim, Sanjida; Mostafa, Ashif Mahmud; Morshed, Azmain; Shaiyaz, Namreen (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.